Gain-of-function missense variant in SLC12A2, encoding the bumetanide-sensitive NKCC1 cotransporter, identified in human schizophrenia. (June 2016) - Merner, Nancy D.; Mercado, Adriana; Khanna, Arjun R.; Hodgkinson, Alan; Bruat, Vanessa; Awadalla, Philip; Gamba, Gerardo; Rouleau, Guy A.; Kahle, Kristopher T.
Abstract: Perturbations of γ-aminobutyric acid (GABA) neurotransmission in the human prefrontal cortex have been implicated in the pathogenesis of schizophrenia (SCZ), but the mechanisms are unclear. NKCC1 ( SLC12A2 ) is a Cl – -importing cation-Cl – cotransporter that contributes to the maintenance of depolarizing GABA activity in immature neurons, and variation in SLC12A2 has been shown to increase the risk for schizophrenia via alterations of NKCC1 mRNA expression. However, no disease-causing mutations or functional variants in NKCC1 have been identified in human patients with SCZ. Here, by sequencing three large French-Canadian (FC) patient cohorts of SCZ, autism spectrum disorders (ASD), and intellectual disability (ID), we identified a novel heterozygous NKCC1 missense variant (p.Y199C) in SCZ. This variant is located in an evolutionarily conserved residue in the critical N-terminal regulatory domain and exhibits high predicted pathogenicity. No NKCC1 variants were detected in ASD or ID, and no KCC3 variants were identified in any of the three neurodevelopmental disorder cohorts. Functional experiments show Y199C is a gain-of-function variant, increasing Cl – -dependent and bumetanide-sensitive NKCC1 activity even in conditions in which the transporter is normally functionally silent (hypotonicity). These data are the first to describe a functional missense variant in SLC12A2 in human SCZ, and suggest that genetically encoded dysregulation of NKCC1 may be a risk factor for, or contribute to the pathogenesis of, human SCZ.